A hipercodificação e a mortificação do “eu”, a docilização dos corpos e o panoptismo na deontologia e no ordenamento disciplinar militar do Estado de São Paulo: um exame sociofilosófico do militarismo policial - Martins, Eliezer Pereira (2017)
Life in the barracks is dictated by a multiplicity of normative commands that organic scan the behavior of the individual-military", particularly when it comes to functional routinization done by the military police. This is a process of interna corporis socialization that acts inside of the dynamics formation of military and police identity, and represents a traditional symbolic capital of institutional power of the military apparatus of the State. In fact, mark symbolically the individuals subject to the police culture, using specific features of "total institution" to the police rows. Thus, the profile of the identity of the military's civilian is gradually the mortification of mechanisms of the "I" conjured up by an instrumental logic of an axiological military discipline hermetically “closed” and distanced, from the point of view of politics, and the values of democracy, republic, and humanities. Given this, here it is claimed that the military "disciplines", in turn, establishes a general system of control and docilization of military conducts closely linked to the Panopticon system, which ensures an efficient and exemplary punishment of acts considered as deviants of military standards. Given this, here it is tried to identify that the hipercodification of the law system of the military police of São Paulo state, in Brazil, was inspired by the speech of the "military-moral". It constitutes the “I” mortification technique by docilization of the military bodies and the disciplinary panoptism. Finally, it is demonstrated here the need to reduce the field of completeness and disciplinary strategies of the legal system of the military police of São Paulo, which leads to the creation of a model of discipline aesthetically military aligned to the interests of society, justice system and the establishment of the fundamental rights of the military police. This kind of discipline needs to be aligned to the construction of a police identity in tune with humanistic values, what marks the originality of the thesis sustained in this work, marked mostly by philosophical musings of Michel Foucault